Traces of Dutch Colonial Heritage in Bekri as a Social Studies Learning Resource - Sabilla, Nabita Deassy; Karsiwan, Karsiwan (Mentari : Journal of Islamic Primary School, 2024)
Bekri Subdistrict is one of the subdistricts in Central Lampung that was administered by a Dutch controleur during the colonial period, assisted by an indigenous demang. This study aims to describe the remnants of the Dutch colonial period in Bekri and to provide historical insight by utilizing these remains as sources of local history learning. These historical remnants serve to remind the community of the importance of preserving and protecting cultural heritage, which must be consciously maintained for the benefit of present and future generations. The colonial remains found in Bekri include buildings, structures, sites, and cultural heritage areas, such as the facilities of PT Perkebunan Nusantara VII (palm oil plantation) and railway stations. This research employed a qualitative approach using a social survey research design based on direct human observation. Data were collected through interviews, observations, and documentation techniques.